2022
DOI: 10.3389/fpls.2022.1082554
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of stress-related signaling molecules affect growth and cannabinoid accumulation in medical cannabis (Cannabis sativa L.)

Abstract: Medical cannabis (Cannabis sativa L.) is a source of bioactive phytochemicals with promising pharmacological and therapeutic applications. Enhancing the accumulation of valuable bioactive compounds is potentially a way of increasing the economic importance of this crop. Signaling molecules like salicylic acid (SA), jasmonic acid (JA), and γ-aminobutyric acid (GABA) are involved in the regulation of plant development and responses to biotic and abiotic stresses. Moreover, several phytohormones regulate plant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Salicylic acid and γ-aminobutyric acid have already been shown to positively impact the expression of THC biosynthetic genes and the content of THC in plants grown under controlled conditions [99]. Methyl jasmonate and salicylic acid applied at 0.1 mM were effective in increasing THCA and CBDA concentrations both in inflorescences and leaves [100]. However, genotype and environmental conditions, as well as pests (shown to impact cannabinoid and terpene content [101]), pose a challenge to the application of C. sativa plants' elicitation on a large scale, i.e., under field conditions, as these factors can contribute to a great variability in secondary metabolite content.…”
Section: Discussionmentioning
confidence: 93%
“…Salicylic acid and γ-aminobutyric acid have already been shown to positively impact the expression of THC biosynthetic genes and the content of THC in plants grown under controlled conditions [99]. Methyl jasmonate and salicylic acid applied at 0.1 mM were effective in increasing THCA and CBDA concentrations both in inflorescences and leaves [100]. However, genotype and environmental conditions, as well as pests (shown to impact cannabinoid and terpene content [101]), pose a challenge to the application of C. sativa plants' elicitation on a large scale, i.e., under field conditions, as these factors can contribute to a great variability in secondary metabolite content.…”
Section: Discussionmentioning
confidence: 93%
“…The primary precursors for cannabinoids are hexanoyl-CoA, a product of the fatty acid synthesis pathway, and geranyl-pyrophosphate, produced through the methylerythritol phosphate pathway, a part of the more general terpenoid biosynthesis pathway [ 9 , 10 ]. Numerous studies clearly demonstrated that stress factors such as mechanical damage, insect herbivory, extreme heat, and drought induce the synthesis of cannabinoids and terpenes in the cannabis plant [ 25 28 ]. The primary role of cannabinoids is believed to be protective, acting as defense chemicals, deterring herbivores, and protecting the plant from UV radiation and environmental stress [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the interaction between the Cannabis oxylipin and cannabinoid pathways has largely been overlooked. Several investigations have sought to increase cannabinoid content using JA or methyl-JA treatments on Cannabis flowers [ 154 ], leaves [ 155 ], or cell cultures [ 156 ] and have been met with mixed results. Studies that analyze oxylipin levels in Cannabis tissues or products have focused on volatiles from above-ground tissues [ 157 ], seeds [ 158 ], or seed oil [ 159 , 160 ] as components of their odor profiles.…”
Section: Discussionmentioning
confidence: 99%